Atlas information system of natural and cultural heritage of Ukraine - Polyvach, Kateryna (Human Geography Journal, 2021)
The purpose of this study is to highlight the conceptual and methodological approaches as well as practical experience in creating of an Atlas Information System of natural and cultural heritage of Ukraine (AIS PiKS) and to outline the directions of its long-term development. AIS PiKS means a problemoriented information system that provides an opportunity to store, systematize and analyze a large amount of accounting and statistical information that will present a modern and clear information picture of the state and trends of the development trends of objects and territories of the country’s natural and cultural heritage and its regions, and present it with traditional and modern means of visualization; to assist the bodies of state administration in the formation and implementation of state policy in the field of natural and cultural heritage, such as accounting, protection, conservation and use of its objects and territories etc. At the first stage of its development, AIS PiKS was reflected in the form of appropriate blocks of the electronic Atlas "Population of Ukraine and its natural and cultural heritage" (hereinafter – the Atlas). The development of the atlas was completed in 2020 by the Institute of Geography of NASU. Among the many scientific and applied tasks that were solved, the focus is on research of their thematic component, among them – the theoretical development of the component structure and content of AIS PiKS, development of conceptual and terminological apparatus, analysis, and visualization of various spatial and descriptive information. The formation of information database AIS PiKS was carried out in the presence of a huge number of potential mapping objects, inefficiently functioning state accounting system of PiKS objects and territories and the need to supplement existing lists with data on spatial localization of mapping objects, visualization of topographic location and necessary attributive (descriptive) information. The need to present a wide range of data from areas related to geography (primarily culture) required the search for new conceptual approaches, methodological solutions, and relevant information sources. As a result, the first in Ukraine specialized thematic maps of ethnocultural, religious and scientific and technical heritage were created, which is a scientific novelty of the Atlas. For the first time in Ukraine, сultural-landscape zoning of Ukraine has been developed at the macro level, thus starting to fill a gap of the absence of domestic developments of this kind. The map "Cultural-landscape zoning of Ukraine" became one of the key topics of the electronic atlas "Population of Ukraine and its natural and cultural heritage". The study identified proposals on the main directions of development and practical application of AIS PiKS. Besides actualization of data, they involves the development of the main ideas and areas of research planned in the Atlas, especially on complex electronic atlases, the deepening of the regional aspect of case studies of cultural and natural heritage through inclusion in the systems of national and regional strategy, spatial development planning, research on integrated study of territory, mapping and development of CLZ of cultural and natural heritage of regions and administrative districts, etc.